Legal Protection Of Early Marriage To Minors In The Perspective Of Law Number 16 Of 2019 Concerning Amendments To Law Number 1 Of 1974 Concerning Marriage - Michael Putra Panjaitan; Deny Guntara; Muhamad Abas (Ipso Jure, 2025)
Early marriage in Indonesia has entered an alarming stage with the number of early marriages continuing to climb as poverty in Indonesia increases. For the poor, early marriage is a pragmatic effort to reduce the economic burden born from the obligation to take care of their children. However, this actually worsens the condition because children who marry early find it difficult to get out of structural poverty. With a normative juridical method, this research is intended to understand the legal dynamics in the context of preventing early marriage in society. From this study, it was found that there was a legal gap in the revision of the Marriage Law and the absence of legal products that function to prevent early marriage so that the number of early marriages continues to increase and responsible actors can avoid their responsibilities by taking advantage of existing legal loopholes